Differences in Mpox and Vaccinia Immunity Induced by Non-Replicating and Replicating Vaccinia-Based Vaccines - Getahun Abate; Krystal Meza; Yinyi Yu; Chase Colbert; Anna Jaunarajs; Azra Blazevic; Daniel F. Hoft; Sharon E. Frey (Vaccines)
Background: The recent global outbreak with clade IIb and the concurrent emergence of clade I mpox virus in Africa show that mpox is a challenging problem. MVA-BN induces low-level mpox-neutralizing antibody responses that wane rapidly. This study was conducted to compare the mpox immunity induced by a replication-competent smallpox vaccine and non-replicating MVA-BN. Methods: Stored sera (n = 302) and PBMCs (n = 244) collected pre-vaccination and at five post-vaccination time points in MVA-BN and six post-vaccination time points in Dryvax clinical trials were used. Antibody titers that neutralized at least 50% of mpox in cell culture were determined by the focus reduction neutralization test (FRNT) 50, and the mpox-specific T cell responses were measured using an IFN-γ ELISPOT assay. Results: The peak geometric fold rise (95% CI) (i.e., the maximum GMFR across all study visits) in the mpox FRNT50 for subcutaneous (SC) MVA-BN, intradermal (ID) MVA-BN, and Dryvax was 22.1 (8.3, 59.1), 18.5 (8.0, 43.1), and 245.8 (100.4, 601.6), respectively. The GMFR at day 180 post-vaccination for MVA-BN (SC), MVA-BN (ID), and Dryvax was 2.4, 2.7, and 64, respectively. The mean (95% CI) peak number of mpox-specific IFN-γ-producing SFCs was 127 (43.1, 238.3), 87.3 (46, 137), and 61.2 (44.3, 77.7) for MVA-BN (SC), MVA-BN (ID), and Dryvax, respectively. On day 180, the mean SFCs in the three groups decreased to 10.8 (−34.4, 3.8), 3.3 (−6.2, 18.6), and 2.2 (−9, 12.5), respectively. Conclusions: The peak mpox-neutralizing antibody titer was >10-fold lower in MVA-BN recipients compared to those who received a replication-competent smallpox vaccine, and the level at day 180 was >20 times lower in MVA-BN recipients. MVA-BN induced similar or higher T cell responses.